How to Get the Teaching Job You Want: The Complete Guide for College Graduates, Teachers Changing Schools, Returning Teachers and Career Changers - Feirsen, Robert; Weitzman, Seth (Routledge, 2023)
Competition for the best teaching jobs is becoming more intense. Since publication of the first edition, when it was mainly the most desirable schools that were deluged by applications, the economic climate has made the teacher market more competitive across the board, and is changing hiring practices. Now extensively revised, this book maintains its place as the most up-to-date book available on job hunting for teachers. The authors cover changes in the educational marketplace; the new mandates about standardized testing and public reporting of student achievement-and what they mean for applicants; how new certification standards and schools' requirements affect career changers; the growing acceptance of on-line applications and electronic portfolios; and provide additional advice for teachers applying to change schools or districts.This is also the only guide written by school administrators. Offering the insights and experience of two authors who do the hiring, it details a step-by-step program for taking charge of your teaching career. How to Get the Teaching Job You Want enables you to:* Match your unique talents to the needs of a particular school* Craft effective cover letters and resumes, using models that address the specific needs of college graduates, teachers changing schools, returning teachers and career changers* Make effective on-line applications* Leverage your achievements as an experienced teacher-or, for graduates or career changers, student teaching, substitute teaching, volunteer work or content knowledge-into a job offer* Locate jobs on-line and discover valuable information about schools, including test results, educational philosophy and names of key administrators* Design a portfolio in book or electronic format to showcase your abilities* Practice interview skills using 100 questions taken from real job interviews* Apply proven strategies for a variety of interview formats, including high stress interviews and performance interviews* Address controversial questions during interviewsThis book covers procedures for applying to elementary, middle and high schools; public, independent, and parochial schools; as well as international and boarding schools. Anecdotes recounting the experiences of real candidates looking for jobs illustrate key points. Access to the authors' web site ensures that you will stay current in a changing job market. This is a vital book for teachers and aspiring teachers who want to achieve their career goals. It will also be invaluable for guidance counselors, psychologists, librarians and other school professionals.